(untitled) (Research, Society and Development, 2021)
The teaching assistantship consists of an extracurricular activity that aims to awaken the interest of students in the practice of teaching and scientific research. In this sense, the present article consists of an experience report of the tutoring experience in an elective course at the Faculty of Medicine of the Federal University of Alagoas through the pandemic scenario caused by the dissemination of the new coronavirus. The purpose of this report, in addition to sharing the experience of the teaching assistants, is to depict the relevance of tutoring for the education of medical students enrolled in the Allergy and Clinical Immunology course, despite the context of remote learning. Tutoring activities took place during the second half of 2020 and the first half of 2021, through synchronous and asynchronous activities in virtual environments. From this perspective, although in a non-traditional way than what it used to be presented, tutoring was able to promote cooperation between teachers and different students, encouraging them to exchange knowledge, in addition to having allowed the overcoming of adversity situations, improvement and adaptation of teaching strategies to a digital format and promoting a better learning experience at graduation, specifically in the area of ​​allergy and clinical immunology.